Lung Inhomogeneities and Time Course of Ventilator-induced Mechanical Injuries. (September 2015) - Cressoni, Massimo; Chiurazzi, Chiara; Gotti, Miriam; Amini, Martina; Brioni, Matteo; Algieri, Ilaria; Cammaroto, Antonio; Rovati, Cristina; Massari, Dario; di Castiglione, Caterina Bacile; Nikolla, Klodiana; Montaruli, Claudia; et al.
<x xml:space="preserve">Abstract</x> Background: During mechanical ventilation, stress and strain may be locally multiplied in an inhomogeneous lung. The authors investigated whether, in healthy lungs, during high pressure/volume ventilation, injury begins at the interface of naturally inhomogeneous structures as visceral pleura, bronchi, vessels, and alveoli. The authors wished also to characterize the nature of the lesions (collapse vs. consolidation). Methods: Twelve piglets were ventilated with strain greater than 2.5 (tidal volume/end-expiratory lung volume) until whole lung edema developed. At least every 3 h, the authors acquired end-expiratory/end-inspiratory computed tomography scans to identify the site and the number of new lesions. Lung inhomogeneities and recruitability were quantified. Results: The first new densities developed after 8.4 ± 6.3 h (mean ± SD), and their number increased exponentially up to 15 ± 12 h. Afterward, they merged into full lung edema. A median of 61% (interquartile range, 57 to 76) of the lesions appeared in subpleural regions, 19% (interquartile range, 11 to 23) were peribronchial, and 19% (interquartile range, 6 to 25) were parenchymal (P < 0.0001). All the new densities were fully recruitable. Lung elastance and gas exchange deteriorated significantly after 18 ± 11 h, whereas lung edema developed after 20 ± 11 h. Conclusions: Most of the computed tomography scan new densities developed in nonhomogeneous lung regions. The damage in this model was primarily located in the interstitial space, causing alveolar collapse and consequent high recruitability.